Formal and Informal Costs of Entering University: How Much are We Ready to Pay? - РощинаЯна Михайловна (Journal of Economic Sociology, 2010)
The paper provides the empirical results of the study, the main idea of which is that entrance to the university costs something. The author identifies several types of such cots, tries to explain the people’s choice of the costs’ relation and to disclose if these costs are alternative or complimentary ones. The factors of these costs and the parents’ readiness to pay them are discussed in the text. The basis for the paper is the special poll, held in April-September in 2001 in Moscow region, Pskov region, Rostov region and Perm region in Russia.